The Effect of Wordwall-Based Interactive Learning Media on Students’ Interest and Learning Outcomes in Social Studies at MTs Hifzhil Qur’an Medan - Lubis, Tiara Ramadhani; Ponidi, Ponidi (Journal of Educational Sciences, 2025)
This study aims to examine the effect of interactive learning media based on Wordwall on students' interest and academic achievement in social studies at MTs Hifzhil Qur'an Medan. A quantitative approach with a quasi-experimental design was employed, involving two class groups: an experimental group using Wordwall and a control group applying conventional learning. Data were collected using a questionnaire to measure students' learning interest and tests to assess academic achievement. The findings indicate a significant difference between the groups. The t-value for learning interest was 4.880, higher than the t-table value of 2.001, and the t-value for academic achievement was 8.225, also exceeding the t-table. Simultaneous testing showed an F-value of 22.391, greater than the F-table value of 2.77, with a significance value of 0.000. These results demonstrate that the application of Wordwall media significantly improves students' interest and learning outcomes. The coefficient of determination (R²) indicates that 54.5% of the effect on learning outcomes is attributable to the Wordwall intervention, while the remaining 45.5% is influenced by other factors.